On the analysis of refinable functions with respect to mask factorisation, regularity and corresponding subdivision convergence - De Wet, Wouter de Vos (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Mathematical Sciences))--University of Stellenbosch, 2007.